ANALISIS PENERAPAN PERHITUNGAN DAN PEMOTONGAN PAJAK PENGHASILAN PASAL 21 UU NOMOR 7 TAHUN 2021 - Aprilia, Baiq Siswari; Fathurrahman, Fathurrahman; Andiana, Baiq Dewi Lita (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2025)
This study aims to analyze the application of the calculation and deduction of Income Tax Article 21 at theRegional Development Planning Agency (BAPPEDA) of West Lombok Regency, as well as its compliancewith the provisions stipulated in Law Number 7 of 2021 concerning Harmonization of Tax Regulations. Theresearch method used is descriptive with a quantitative approach, which involves collecting data related topayroll lists, tax calculations, and proof of tax deductions from 42 permanent employees in 2023. The results ofthe study show that there are significant differences between the calculations made by the BAPPEDA of WestLombok Regency and the calculations based on applicable tax provisions. Some of the main causes of thediscrepancy are the non-inclusion of the 5% job cost component in the calculation of gross income and errorsin filling in the payroll elements and proof of tax deductions. As a result, there is an excess withholding ofIncome Tax Article 21 which has an impact on inaccurate tax reporting, even though the state is not directlyharmed. This study concludes that improving understanding of tax regulations and implementing a moreintegrated accounting system can help BAPPEDA of West Lombok Regency in improving the accuracy of taxcalculations, deductions, deposits, and reporting. Recommendations submitted include tax training for relatedemployees and updating the financial administration system according to tax standards